ANALISIS POSTUR TUBUH PEKERJA PROSES PENGGORENGAN PADA UMKM KERUPUK RASA PUNCAR TOWER PIAYU - Khairi, Defiki; Zetli, Sri (Computer Science and Industrial Engineering, 2025)
Muscoskeletal Disorder is one of the causes of poor work posture during work activities. Efforts to minimize this complaint are by identifying, evaluating, and improving the products that are the work media and body posture while working. This study is a study conducted on the three work activities at UMKM Kerupuk Khas Bandung Rasa Puncar Tower Piayu Batam such as sorting crackers, frying and filtering crackers. Based on the results of body posture with Rapid Entire Body Assessment (REBA) the three activities of sorting crackers, frying and filtering crackers are high-risk activities are frying activities with a bent position when taking or moving raw cracker materials to the fryer or other places can put excessive pressure on the lower spine (lumbar). If workers often lift materials in a non-ideal position, the risk of back and shoulder muscle injuries increases. The improvements made by the researcher were to design a frying table using anthropometric data with the Front Arm Length (JTD) used for a frying pan diameter of 80 cm. Standing Elbow Height (SEL) is used as a benchmark for table height with a result of 100 cm. Hand Span (RT) is used for the length of the cracker frying table with 240 cm by placing 2 frying pans for 2 cracker frying workers.